TRUE AND HOLOGRAPHIC KNOWLEDGE - Reihenova, Austra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article deals with the direction of philosophy - epistemology, it is a study of knowledge and cognition. The main aspects of epistemology are the dimensions of knowledge, the sources of knowledge and the reliability of knowledge. The education system deals with the acquisition of knowledge, the use of various sources of knowledge and the reflection of the reliability of knowledge in curricula. Learning content includes knowledge that helps to find, create and use new knowledge. Modern curriculum requires a review of all school knowledge, conceptual and factual apparatus of school education. Mankind has accumulated a tremendous amount of knowledge. Essential preconditions for the selection of educational content: that the acquired knowledge covers the basics of various sciences; so that the curriculum covers different types of knowledge; that the student acquires knowledge from different sources of knowledge and uses different dimensions of knowledge; so that in order to explain the processes taking place in the universe, the student uses the true knowledge, which is formed on the laws of eternal harmony, is structured and maintains the whole of the world. The topicality of the article is related to the modern study content, which is based on true structured knowledge. The aim of the article is to review the content of the curriculum so that students have access to quality knowledge that is organized in a system and considered as a whole, and explains the processes taking place in the world.